2020
DOI: 10.3171/2020.2.spine191363
|View full text |Cite
|
Sign up to set email alerts
|

Neutral cervical sagittal vertical axis and cervical lordosis vary with T1 tilt

Abstract: OBJECTIVEThe authors conducted a study to determine whether a change in T1 tilt results in a compensatory change in the cervical sagittal vertical axis (SVA) in a cadaveric spine model.METHODSSix fresh-frozen cadavers (occiput [C0]–T1) were cleaned of soft tissue and mounted on a customized test apparatus. A 5-kg mass was applied to simulate head weight. Infrared fiducials were used to track segmental moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Most of the studies on cervical sagittal balance were clinical observational studies. Only one cadaveric experiment of Hofler et al (2020) reported that T1 tilt was Frontiers in Bioengineering and Biotechnology frontiersin.org closely associated with cervical SVA (CSVA) and lordosis, but their study did not examine the effect of T1 tilt change in ACF.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the studies on cervical sagittal balance were clinical observational studies. Only one cadaveric experiment of Hofler et al (2020) reported that T1 tilt was Frontiers in Bioengineering and Biotechnology frontiersin.org closely associated with cervical SVA (CSVA) and lordosis, but their study did not examine the effect of T1 tilt change in ACF.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on cervical sagittal balance were clinical observational studies. Only one cadaveric experiment of Hofler et al (2020) reported that T1 tilt was closely associated with cervical SVA (CSVA) and lordosis, but their study did not examine the effect of T1 tilt change in ACF. Our study was in well agreement with Hofler et al (2020) , and our results indicated that ACF may bring slightly more influence to SVA than C2-C7 Cobb angle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations